The Effect of Mosque Da'wah on the Level of Islamic Social Financial Literacy for Jama'ah in South Tangerang - Reksawan, Diant; Yandri, Pitri (Dinasti International Journal of Management Science, 2025)
The overall state of Islamic financial literacy in Indonesia is currently suboptimal, primarily attributed to the underutilization of government initiatives aimed at enhancing Islamic financial literacy. Remarkably, mosques, which possess the potential to significantly and directly contribute to community enlightenment, have yet to serve as effective conduits for the dissemination of government programs targeting the improvement of Islamic financial literacy. Presently, there is a dearth of research focusing on the impact of mosque da'wah on Islamic financial literacy levels, as well as investigations examining the specific entities within mosques regarding Islamic social financial literacy. This study seeks to bridge this research gap by amalgamating these two dimensions, employing a descriptive quantitative approach through the application of Structural Equation Modeling (SEM) utilizing the Smart PLS version 3.0 application. The findings of this study underscore that the level of Islamic social financial literacy is positively and significantly influenced by da'i (actors), maddah (message), and thoriqoh (method). However, while wasilah (media da'wah) exerts an influence on the level of Islamic social financial literacy, its impact is comparatively less robust. Additionally, the study reveals that respondents exhibit a relatively modest degree of Islamic social financial literacy. These findings carry significant implications, emphasizing the potential of mosques as pivotal centers for the enhancement of Islamic social financial literacy.